The Prevalence of Salmonella spp. in Two Arctic Fox (Alopex lagopus) Farms in Poland - Jan Siemionek; Konrad Przywara; Anna Szczerba-Turek (Animals, 2020)
The objective of the study was to determine the occurrence of Salmonella spp. infections in two Arctic fox (Alopex lagopus) farms in Poland, and to analyse the correlations between animals that tested positive for Salmonella spp and breeding results. Faecal samples were taken from 1094 clinically healthy blue foxes from the basic stock of farms A and B. Salmonella spp. were detected in 18.06% (56/310) of the samples collected in farm A and in 15.94% (125/784) of the samples collected in farm B. All isolated strains belonged to S. enterica subsp. enterica serotypes Salmonella Saintpaul (S. Saintpaul), Salmonella Reading (S. Reading), and Salmonella Heidelberg (S. Heidelberg). All three serotypes are typically isolated from commercial poultry flocks. Salmonella spp. infections significantly increased the risk of female infertility, but further research is needed to confirm the results. This is the first report on the prevalence of S. Heidelberg, S. Saintpaul, and S. Reading in faecal samples collected from Arctic fox (Alopex lagopus) farms in Poland.